PENERAPAN PAJAK PENGHASILAN BADAN BERDASARKAN UNDANG-UNDANG NOMOR 28 TAHUN 2007 DAN HARMONISASI PERPAJAKAN - Lubis, Asep Ridwan; Dinanti, Dinda (Journal of Financial Economics & Investment, 2022)
Corporate income tax is one of the sources of tax that contributes a lot to state revenue. The application of taxes carried out by several companies certainly cannot be separated from the efforts made by the management to comply with the applicable tax laws and regulations. This article aims to provide a theoretical review as well as a brief summary of the application of Corporate Income Tax (PPh) found in several companies in Indonesia based on the KUP Law and the HPP Law. Data was collected through a qualitative approach which is a literature study. The type of data used is secondary data where the data is obtained indirectly. The results of the study indicate that the application of corporate income tax carried out by companies in Indonesia has made adjustments to changes in the policies of the applicable laws and regulations. The tax rate will also be more effective and efficient if the company uses the calculation of the Final Corporate Income Tax Rate, but currently there are not many literature studies that use the application of the 22% Final Corporate Income Tax.